The Importance of Sight Word Recognition to Improve Reading Fluency - Dini Amalia (Institut Agama Islam Tarbiyatut Tholabah, 2022)
Reading is one of crucial skills for mastering English proficiency. It does not only involve the ability to pronounce correctly, but also to understand the text as a whole. It does not only have tremendous power when it comes to fuelling the development of all aspects of language ability, its importance to the entirety of a human life cannot really be overstated nowadays. The fact that English is full of silent letters and unexpected sounds provoke the learners to simply memorize the spelling of a word in order to recognize its written form in the future. The inconsistency between letters and phonemes, more than one way to spell the same sound, are the basic problems for the learners, especially beginners. Dealing with the matter of inconsistency, the technique and strategy to learn English is gradually upgraded. This study applies descriptive analysis method to reveal the sight word recognition strategy focusing on upgrading the competency in mastering vocabularies and reading. The findings show that by activating the recognition of sight word and associating phoneme (sounds) and grapheme (letters), learners tend to be more easily figure out the words and understand the text. By having sight words vocabularies through orthographic mapping, the process of understanding reading text becomes easier. Learners know the words more quickly since sight word recognition improves reading fluency and efficiency. In its process, as learners see the word, they automatically activate the recognition of its meaning and pronunciation at the same time.